Wind shear and differential upwelling along the South Western tip of Africa - Jury, Mark Robert (Department of Oceanography, 2016)
Along the SW tip of Africa (30-35° S, 17-20° E) topographic irregularities shear the wind stress field giving rise to coastal upwelling with an alongshore variability. The relationship between wind shear and differential upwelling is established using a blend of oceanographic and meteorological investigations. Mesoscale aerial survey case studies form the observational basis from which the spatial variations in winds and upwelling are compared. Coastal winds, controlled by the pressure gradient between the South Atlantic Anticyclone and a summertime interior low, become modulated through interactions with the circumpolar jet stream. Low level winds accelerate over portions of the southern Benguela current region through deflections forced by three pronounced capes, two with mountain ridges exceeding 1000 m. Selected case studies are utilized to contrast the characteristics of deep and shallow wind flow, and the exposed and sheltered offshore regions. The spatial variability of the low level wind and sea surface temperature fields is correlated by means of aerial survey techniques applied at alongshore spacings of 10 to 50 km. Vertical transect and profile data collected at altitudes up to 1 km illustrate the variable depth of wind flow. Vertical wind shear controls the interaction of topography and winds. Field results show that vertical shears of -2 (10⁻²)s⁻¹ produce horizontal wind vorticities of -6 (10⁻⁴)s⁻¹ and alongshore sea surface temperature gradients of 1°C (10km)⁻¹ , a characteristic of summertime upwelling in the southern Benguela region.